2020
DOI: 10.1136/rmdopen-2020-001175
|View full text |Cite
|
Sign up to set email alerts
|

Achieving sustained minimal disease activity with methotrexate in early interleukin 23-driven early psoriatic arthritis

Abstract: ObjectivesMethotrexate (MTX) is currently the recommended first-line therapy for treating psoriatic arthritis (PsA), despite lacking clear evidence. No estimates of efficacy of MTX in usual care and no clear MTX responsive clinical or laboratory variables are currently available. This study describes the response to MTX monotherapy in newly diagnosed patients with PsA in usual care. Second, we compared clinical variables and cytokine profiles in patients responding and not responding to MTX monotherapy.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…IL-23 is involved in the activation and proliferation of Th17 cells linked to sustained inflammatory responses in the skin and joints in PsA, and anti-IL-23 antibodies have shown efficacy in PsO and PsA 2 12. Patients with early PsA who do not achieve MDA with standard methotrexate therapy have higher levels of IL-23 than those who respond to methotrexate 13…”
Section: Introductionmentioning
confidence: 99%
“…IL-23 is involved in the activation and proliferation of Th17 cells linked to sustained inflammatory responses in the skin and joints in PsA, and anti-IL-23 antibodies have shown efficacy in PsO and PsA 2 12. Patients with early PsA who do not achieve MDA with standard methotrexate therapy have higher levels of IL-23 than those who respond to methotrexate 13…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have specifically analysed the efficacy and safety of the selected drugs in patients with early PsA [ 91 ]. Inadequate response with MTX monotherapy in this sub-group of patients has been reported [ 20 , 126 ], but a RCT and open-label extension recently published observed that around half of patients with early PsA achieved remission with initial combination treatment of MTX + TNF inhibitors that was maintained with MTX monotherapy afterwards [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings were supported by studies that classified the same patients using both metrics, allowing residual disease to be more accurately compared between ‘equivalent’ groups. In the DEPAR study for example, prevalence of > 1 residual tender or swollen joints, > 1 tender entheseal points, PASI > 1, PtP VAS > 15, PtGA VAS > 20 or HAQ-DI > 0.5 was lower among MDA-achievers than among DAPSA LDA-achievers [ 22 , 45 , 67 – 70 ]. Across the MDA metric and DAPSA, we noted that these listed thresholds were most often exceeded for PASI, PtP and PtGA.…”
Section: Discussionmentioning
confidence: 99%